Economy and technology as influential factors for digital piracy sustainability: An Indonesian case - Wulandari, Hesty (Elsevier Ltd., 2014)
This research aims to figure out whether or not economy and technology are the reasons why digital piracy keeps going on.For this research, we use research conducted by Battacharje (2003) as the main reference. In this research, we examine economic and technological factors within 12 indicators, resulting that in average, most respondents agree that the reason why they keep doing digital piracy is its influence by economic and technology factors.